2006
DOI: 10.1021/jf0605446
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vineyard Location and Vine Water Status on Fruit Maturation of Nonirrigated Cv. Agiorgitiko (Vitis viniferaL.). Effects on Wine Phenolic and Aroma Components

Abstract: The influence of site on grape and wine composition was investigated for Vitis vinifera L. cv. Agiorgitiko in the Nemea appellation area in southern Greece. Three nonirrigated plots were studied during the 1997 and 1998 vintages, which were typically very hot and without summer rainfall. Vines were subjected to different water regimens as a result of the variation of soil water-holding capacity and evaporative demand. Vine water status was determined by means of predawn leaf water potential. Differences in vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
169
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(195 citation statements)
references
References 38 publications
20
169
0
6
Order By: Relevance
“…O tratamento IP ao final do ciclo apresentou conteúdos de açúcares semelhantes aos demais tratamentos com restrições hídricas, podendo boa parte dos seus fotoassimilados terem sido desviados para a atividade vegetativa e/ou armazenamento nos ramos, raízes e braços durante o período de pós-veraison, desviando assim, os açúcares que se acumulariam nas bagas (KOUNDOURAS et al, 2006). Essa afirmação ainda pode ser confirmada por não ter havido diferença no teor de sólidos solúveis entre as estratégias hídricas na colheita e um maior crescimento vegetativo para o tratamento IP foi visualizado na área experimental.…”
Section: Resultsunclassified
“…O tratamento IP ao final do ciclo apresentou conteúdos de açúcares semelhantes aos demais tratamentos com restrições hídricas, podendo boa parte dos seus fotoassimilados terem sido desviados para a atividade vegetativa e/ou armazenamento nos ramos, raízes e braços durante o período de pós-veraison, desviando assim, os açúcares que se acumulariam nas bagas (KOUNDOURAS et al, 2006). Essa afirmação ainda pode ser confirmada por não ter havido diferença no teor de sólidos solúveis entre as estratégias hídricas na colheita e um maior crescimento vegetativo para o tratamento IP foi visualizado na área experimental.…”
Section: Resultsunclassified
“…Elevated temperature clearly decreases the concentration of malic acid, whereas grapevines grown in cool climates have a higher malic acid concentration in their berries (Keller et al 2005, Koundouras et al 2006, Pereira et al 2006. The impact of water stress on berry malic acid concentration is less clear, and increases (Lòpez et al 2007), decreases (Koundouras et al 2006, Salon et al 2005, or even no change (Esteban et al 1999) have been reported. Tartaric acid concentration, on the other hand, does not appear to be significantly affected by temperature or water stress (Parra et al 2010).…”
Section: Organic Acidsmentioning
confidence: 99%
“…Several studies have demonstrated a positive association between temperature and seed number or total proanthocyanidin concentrations per berry at harvest (Del Rio & Kennedy, 2006;Ewart & Kliewer, 1977). The influence of temperature on total acidity has been widely discussed (Koundouras et al, 2006) and higher concentrations have been reported in grapes grown in cool regions than that of grapes from warm regions (Lakso & Kliewer, 1975). In the present study, the temperature of Zhangye was moderate when compared with that of Wuwei and Jiayuguan, and the low temperatures and GDD of Jiayuguan might have resulted in the low concentrations of phenols (Table 3).…”
Section: Climatic Conditionsmentioning
confidence: 43%